COVID-19: A Multidisciplinary Review - Chams, Nour; Chams, Sana; Badran, Reina; Shams, Ali; Araji, Abdallah; Raad, Mohamad; Mukhopadhyay, Sanjay; Stroberg, Edana; Duval, Eric J.; Barton, Lisa M.; Hajj Hussein, Inaya (Frontiers in Public Health, 2020)
Coronaviruses are known to cause severe and fatal illness in humans. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a novel coronavirus that is responsible for the 2019-20 pandemic. In this comprehensive review, we discuss the current published literature surrounding the SARS-CoV-2 virus. We examine the fundamental concepts including the origin, virology, pathogenesis, clinical manifestations, diagnosis, laboratory, radiology, and histopathologic findings, complications, and treatment. Given that much of the information has been extrapolated from what we know about other coronaviruses including severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV), we identify and provide insight into controversies and research gaps for the current pandemic to assist with future research ideas. Finally, we discuss the global response to the coronavirus disease-2019 (COVID-19) pandemic and provide thoughts regarding lessons for future pandemics.